VO2 Kinetics During Heavy and Severe Exercise in Swimming - Pessoa Filho, D. M.; Alves, F. B.; Reis, J. F.; Greco, C. C.; Denadai, B. S. [UNESP] (Georg Thieme Verlag Kg, 2012)
The purpose of this study was to describe the VO2 kinetics above and below respiratory compensation point (RCP) during swimming. After determination of the gas-exchange threshold (GET), RCP and VO2max, 9 well-trained swimmers (21.0 +/- 7.1 year, VO2max = 57.9 +/- 5.1 ml. kg(-1).min(-1)), completed a series of "square-wave" swimming transitions to a speed corresponding to 2.5% below (S-2.5%) and 2.5% above (S+2.5%) the speed observed at RCP for the determination of pulmonary VO2 kinetics. The trial below (similar to 2.7%) and above RCP (similar to 2%) was performed at 1.28 +/- 0.05 m.s(-1) (76.5 +/- 6.3% VO2max) and 1.34 0.05 m.s(-1) (91.3 +/- 4.0% VO2max) respectively. The time constant of the primary component was not different between the trials below (17.8 +/- 5.9 s) and above RCP (16.5 +/- 5.1 s). The amplitude of the VO2 slow component was similar between the exercise intensities performed around RCP (S-2.5% = 329.2 +/- 152.6 ml.min(-1) vs. S+2.5% = 313.7 +/- 285.2 ml.min(-1)), but VO2max was attained only during trial performed above RCP (S-2.5% = 91.4 +/- 5.9% VO2max vs. S+2.5% = 103.0 +/- 8.2% VO2max). Thus, similar to the critical power during cycling exercise, the RCP appears to represent a physiological boundary that dictates whether VO2 kinetics is characteristic of heavy- or severe-intensity exercise during swimming.
Keywords: slow component; exercise intensity domains; front crawl